2015 IEEE International Electric Machines &Amp; Drives Conference (IEMDC) 2015
DOI: 10.1109/iemdc.2015.7409171
|View full text |Cite
|
Sign up to set email alerts
|

Direct instantaneous torque and force control: A novel control approach for switched reluctance machines

Abstract: Switched-reluctance technology is appealing to the automotive industry due to its cost efficiency. Conventional research focuses on the two main issues torque ripple and acoustic noise. However, control schemes usually only address one of these two issues at a time. This paper unifies the approaches of direct instantaneous torque control and direct instantaneous force control to simultaneously tackle the two central drawbacks of the switched reluctance machine.A searching algorithm was used to determine approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Although the mode-0 noise is indeed reduced with the above methods, the torque ripple is inevitably introduced since the radial force and torque characteristics differ a lot. To mitigate the radial force and torque ripple simultaneously, [195], [196] rearranged the radial force reference for the two conducting phases during the commutation period to reduce the torque ripple, at the cost of increased RMS current value when compared to the conventional method. Alternatively, [197]- [199] slightly modified the torque ripple minimization reference current by coordinating with the direct force controller, so the vibration is significantly reduced and the toque ripple is kept almost the same when compared with the results of torque ripple minimization controller.…”
Section: Direct Instantaneous Force Controlmentioning
confidence: 99%
“…Although the mode-0 noise is indeed reduced with the above methods, the torque ripple is inevitably introduced since the radial force and torque characteristics differ a lot. To mitigate the radial force and torque ripple simultaneously, [195], [196] rearranged the radial force reference for the two conducting phases during the commutation period to reduce the torque ripple, at the cost of increased RMS current value when compared to the conventional method. Alternatively, [197]- [199] slightly modified the torque ripple minimization reference current by coordinating with the direct force controller, so the vibration is significantly reduced and the toque ripple is kept almost the same when compared with the results of torque ripple minimization controller.…”
Section: Direct Instantaneous Force Controlmentioning
confidence: 99%
“…The implementation of this switching strategy plays an important role in minimizing the torque ripple. In [10,16], the torque pulsations which contributes to torque ripple was largely reduced using DITC. Simulation results showed that torque ripple was reduced to approximately 38% of the machine average torque of 40Nm.…”
Section: ) Direct Instantaneous Torque Controlmentioning
confidence: 99%
“…Na literatura são encontrados diferentes algoritmos usados com o CDTI [24,109,111,115]. Em [115] foi implementado um controle direto de torque e força instantâneos, no qual tanto o torque quanto a força radial são controlados com o perfilamento do fluxo magnético concatenado.…”
Section: Máquinas De Estado Para O Cdtiunclassified
“…Na literatura são encontrados diferentes algoritmos usados com o CDTI [24,109,111,115]. Em [115] foi implementado um controle direto de torque e força instantâneos, no qual tanto o torque quanto a força radial são controlados com o perfilamento do fluxo magnético concatenado. Em [111] um controlador PI é adicionado ao sistema de controle para minimizar as ondulações de torque, entretanto esta abordagem torna a resposta do sistema mais lenta.…”
Section: Máquinas De Estado Para O Cdtiunclassified